Sistem Pakar Untuk Menentukan Departemen Sesuai Kepribadian Calon Karyawan dengan Menggunakan Metode Forward Chaining - Andriyanto, Lely Panca; Wahyu, Meidy Fajar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Human Resource Management (HRD) is an important aspect in ensuring the success of an organization, where the placement of employees who match their personality and skills is a key factor in increasing productivity and reducing turnover rates. This study aims to build a desktop-based expert system using the Forward Chaining method, where the inference process begins by matching personality trait facts from test results to rules (IF-THEN knowledge base) to produce conclusions in the form of recommendations for the most suitable department. as an objective tool in the process of placing new employees based on personality test results, where the system is designed to match the personality characteristics (Sanguine, Melancholy, Choleric, Phlegmatic) of prospective employees with the specific needs of each department. The results of functional testing and validation show that the system built has an accuracy rate of 92% from 50 employee data. The system built is able to provide employee placement recommendations faster with a time efficiency rate of 93.33%. The implementation of this system is a significant contribution in increasing the effectiveness of HRD decision making through the use of artificial intelligence technology.